International Chocolate Market - Vlahović Branislav, Puškarić Anton, Elenov Riste (Департман за економику пољопривреде и социологију села Пољопривредног факултета Универзитета у Новом Саду, 2022)
The paper analyzes the changes in the international chocolate market. The aim of the paper is to analyze the international trade and the largest exporters and importers of chocolate in the world. The data used in the research were obtained from the database of the International Trade Center (ITC) for the period 2016-2020. The average world’s export of chocolate was 5.8 million tons, with a trend of stagnation at a rate of 0.66% per year. The largest exporter is Germany with 878 thousand tons, accounting for 15% of the world’s export. The largest importer is the United States with 670 thousand tons, which is 11.5% of the world’s import. Five multinational companies account for approximately half of the total market share in the world: Mars (14.4%), Ferrero (10.4%), Mondelez International (9.4%), Meiji (7.8%) and Hershey (6.4%). The global chocolate market is expected to grow at a rate of 4.78% to reach a total value of 182 billion US dollars by 2025.
МЕЂУНАРОДНО ТРЖИШТЕ ЧОКОЛАДЕ
Keywords: chocolate, international trade, export, import, consumption